A systematic study and framework of fringe projection profilometry with improved measurement performance for in-situ LPBF process monitoring. (15th March 2022) - Zhang, Haolin; Vallabh, Chaitanya Krishna Prasad; Xiong, Yubo; Zhao, Xiayun
Highlights: Established comprehensive framework of fringe projection profilometry (FPP) for LPBF-AM. Enhanced FPP measurement performance in the application scenario of LPBF. Improved phase wrapping and unwrapping by pixel-wise correction and applying DFT. Comprehensive measurement uncertainty calculations for the LPBF-specific FPP. Quantitative comparison & validation of FPP measurement against standard equipment. Abstract: Fringe Projection Profilometry (FPP) is a cost-effective and non-invasive technology that has been shown to measure finer features. In this work, we developed an in-situ FPP method to measure the dynamic topography of powder bed and printed layer during Laser Powder Bed Fusion (LPBF) additive manufacturing (AM) process. A systematic study towards developing a comprehensive framework of LPBF-specific FPP is demonstrated to enhance and evaluate the performance of applying FPP for in-situ LPBF monitoring, including 1) a modified sensor model with localized correction; 2) improved phase unwrapping with FFT filtering 3) quantitative uncertainty analysis; and 4) experimental validation with ex-situ characterization. The developed LPBF-specific FPP system and methods are implemented on a commercial LPBF-AM machine, achieving better accuracy, more robustness, and increased field of view while maintaining sufficient measurement range and decent resolution, in contrast to literature methods. The established FPP framework will facilitate the development of closed-loop control strategies for advancing LPBF based AM.